Teori dan Tipe Perubahan Hukum Islam Menurut Abdullah Ahmad al-Na’im - Izomidin Izomidin (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2010)
Al-na’im has reconstructed the old legal theory – the theory of nasakh – with a new theory, namely the reverse nasakh or the theory of Islamic legislation evolution in order to revive the eliminated verses caused by the traditional nasakh. When there is verse contradicts to the benefit humankind this nash should be ignored and finds another nash which is more relevant. Thus, the public law of Sharia is in function to meet the demand of needs and course of development.